Animal Rabies in Nepal and Raccon Rabies in Albany County, New York - Yadav, Shankar (My University, 2012)
Rabies is a fatal viral disease that has existed since the antiquity, and is prevalent throughout the world. Wild animals contribute to the spread of this disease to humans and animals in developed nations; however, canines are responsible in transmitting to humans, mostly in Asia and Africa. About 96% of human rabies cases are attributed to dog bites. Annually, 55,000 people (56% in Asia, 44% in Africa) in the world die of rabies. In Nepal, from 2000-2009, 59 districts (out of 75) had the cases of rabies in dogs, cattle, buffaloes, horses, goats, pigs, and cats. Altogether 1713 animal rabies cases were found. The plain and hill areas, where 90% of population resides, were mostly infected. The sixteen districts in high hills did not have any cases. The canine breeding season seems very effective in spreading this disease due to high contact rates. February (n=250) had the highest number of cases, and May (n=89) had the least. Cattle (35.5%) were the mostly affected species, and dogs (32%) ranked second. In Albany County (New York), 74.2% (605/815) of samples from suspected raccoons were (rabies) positive through Fluorescent Antibody test. Females accounted for 57% of the positive cases, and there was an association between gender and positive test results (p<0.01). February (93%) had the highest percentage of cases, and July had the least. Through logistic regression model, it was found that the observed raccoon’s behaviors were associated with the test results. Raccoons that showed the aggression against “domestic animals” were 4 times more likely to be tested as positive rabies case (p<0.0001). The “unafraid” behavior of raccoons were 2.34 times more likely to be tested as positive rabies case (P=0.0094). Those raccoons, which were “active by day time,” were 1.4 times more likely to be tested positive in the diagnosis of brain samples (p=0.0045). The “abnormal (n=141)” sign was associated with a protection from being test-positive with a risk 0.65 times (OR=0.654, CI=0.44, 0.972) as likely to be confirmed as rabid (p=0.0358). Human aggression (n=67, p=0.1177), wild animal aggression (n=12, p=0.6124), and object aggression (n=25, p=0.4036) were not significantly associated with the test results.
Keywords: Rabies; Raccon rabies; Viral disease; Zoonosis; Public Health (0573)